Working with Human Thinking in Developing Intelligent Technologies - Pertti SAARILUOMA; Antero KARVONEN; Jose CAÑAS; Jaana LEIKAS (Communications of International Proceedings, 2024)
Artificial intelligence and robotics are becoming part of everyday life and work. They tend to support or replace human work in industrial processes, as intelligent artefacts can perform tasks that previously relied on human information processing. To develop smart technologies more successfully as a substitute for human work, they should be developed using research on human thinking, based on the analysis, mimicking and modelling of human thought processes. This paper discusses thought process analysis, i.e., qualitative and quantitative study of thinking, cognitive mimetics, i.e., the imitation of human information processes by machines, and human digital twins, i.e., the computational modeling of human thought processes in the design of new technological solutions.  These are discussed as conceptual and methodological tools for the creation of intelligent objects.
Keywords: Artificial intelligence; thinking; cognitive mimetics; human digital twins.